The Relationship between Serum NT– Pro-BNP Levels and Prognosis in Patients with Systolic Heart Failure - Sepideh Sokhanvar; Mahdiye Shekhi; Saeedeh Mazlomzadeh; Zahra Golmohammadi (Journal of Cardiovascular and Thoracic Research, 2011)
Introduction: Most studies reported using N-terminal pro-brain natriuretic peptide (NT-proBNP) in diagnosis of heart failure but there is controversy about use of these tests in determining prognosis and classification of severity of heart failure. The objective of this study was to determine the value of plasma NT-proBNP levels assessment in evaluation of mortality and morbidity of patients with systolic left ventricular dysfunction. Methods: A cohort study was performed in 150 patients with heart failure since September 2009 until February 2010. The patients were followed for 6 months to assess their prognosis. Patients were divided into two good and bad prognosis groups according to severity of heart failure in New York Heart Association (NYHA) class and frequency of hospital admission and mortality due to cardiac causes. Patients with good prognosis had ≥1 admission or no mortality or NYHA class ≥2 and patients that had one of this criteria considered as bad prognosis groups. Pro-BNP levels were measured at baseline and left ventricular ejection fraction (LVEF) was estimated with echocardiography. Data was analyzed with using Chi-square, t-test, ANOVA, Kruskal-Wallis tests. Results: In patients with heart failure that enrolled in this clinical study, ten patients were lost during follow-up. The mean of NT-proBNP is significantly correlated with ejection fraction (p=0.003) and NYHA class (p<0.001). In our study among 140 patients who were follow-up for 6 months, 11(9.7%) of individuals died with mean NT-proBNP of 8994.8±8375 pg/ml, in survived patients mean NT-proBNP was 3756.8±5645.6 pg/ml that was statistically significant (P=0.02). Mean NT-proBNP in the group with good prognosis was 2723.8±4845.2 pg/ml and in the group with bad prognosis was 5420.3±6681 pg/ml, difference was statistically significant (P=0.0001). Conclusion: Our study in consistent with other studies confirms that NT-proBNP is significantly correlated with mortality and morbidity. This could be predicting adverse out come and stratification in patients with heart failure. It is recommended that more research be performed in Iran.